Draft genome sequence of the cyanobacterium Sphaerospermopsis aphanizomenoides BCCUSP55 from the Brazilian semiarid region reveals potential for anti-cancer applications - Lorenzi, Adriana Sturion; Bonatelli, Maria Letícia; Varani, Alessandro M. [UNESP]; Quecine, Maria Carolina; Bittencourt-Oliveira, Maria do Carmo (Springer Nature, 2022)
Sphaerospermopsis aphanizomenoides is a filamentous nitrogen-fixing and bloom-forming cyanobacterium, which biomass can fertilize natural water with nutrients, especially through nitrogen fixation. The Sphaerospermopsis aphanizomenoides strain BCCUSP55 was previously isolated from a water supply reservoir in the Brazilian semiarid region, and its draft genome assembly coupled with the gene contents are reported here. The obtained BCCUSP55 draft genome comprised 254 scaffolds with a genome size estimated of 6,096,273 bp. In addition, it has 5250 predicted coding sequences (CDS) and the G + C content is 38.5%. Further, the BCCUSP55 draft genome presented the putative nocuolin A gene complete cluster, a natural oxadiazine that triggers apoptosis in human cancer cells. Thus, our results contribute to extend the knowledge on the genus Sphaerospermopsis and reveal its biotechnological potential.
Keywords: Anti-cancer drugs; Biotechnology; Nitrogen fixation; Secondary metabolites